2018
DOI: 10.1093/nar/gky093
|View full text |Cite
|
Sign up to set email alerts
|

Lineage specific transcription factors and epigenetic regulators mediate TGFβ-dependent enhancer activation

Abstract: During neurogenesis, dynamic developmental cues, transcription factors and histone modifying enzymes regulate the gene expression programs by modulating the activity of neural-specific enhancers. How transient developmental signals coordinate transcription factor recruitment to enhancers and to which extent chromatin modifiers contribute to enhancer activity is starting to be uncovered. Here, we take advantage of neural stem cells as a model to unravel the mechanisms underlying neural enhancer activation in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 87 publications
(103 reference statements)
2
41
0
Order By: Relevance
“…These data suggest that the observed increase in αKG bioavailability promotes H3K27me2 demethylation at myofibroblast-specific genes in order to promote differentiation. Further evidence in support of our working hypothesis are recent reports suggesting that JMJD3, a JmjC H3K27me2 demethylase with loci specificity, i.e., recruitment to lineage-specific genes, is dependent upon interaction with SMADs 61,62 . Since SMAD2/3 is a canonical transcription factor for TGFβ signaling and myofibroblast activation, it’s intriguing to hypothesize that this interaction may provide myofibroblast-specific demethylation patterns in our model.…”
Section: Discussionsupporting
confidence: 81%
“…These data suggest that the observed increase in αKG bioavailability promotes H3K27me2 demethylation at myofibroblast-specific genes in order to promote differentiation. Further evidence in support of our working hypothesis are recent reports suggesting that JMJD3, a JmjC H3K27me2 demethylase with loci specificity, i.e., recruitment to lineage-specific genes, is dependent upon interaction with SMADs 61,62 . Since SMAD2/3 is a canonical transcription factor for TGFβ signaling and myofibroblast activation, it’s intriguing to hypothesize that this interaction may provide myofibroblast-specific demethylation patterns in our model.…”
Section: Discussionsupporting
confidence: 81%
“…However, how KDM6A orchestrate p300 and BRD4 recruitment at super-enhancers through shaping chromatin environment and whether its activity requires pre-priming of chromatin accessibility by other pioneer transcription factors need to be further explored. In addition to KDM6A, KDM6B has also been implicated in enhancer regulation in different biological processes 34 , 35 , but whether they act redundantly or non-redundantly in shaping enhancer states remain elusive. Interestingly, current study showed that although KDM6A and KDM6B regulate some target genes in similar manner in HCT116 cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse NSCs were prepared from cerebral cortices of C57BL/6J mouse fetal brains (embryonic day [E]12.5). They were cultured in poly-D-lysine (5 μg/mL, 2 h, 37°C) and laminine (5 μg/mL, 4 h, 37°C) precoated dishes (53,54). Cells were maintained in culture as previously described (55) with fibroblast growth factor (FGF) and epidermal growth factor (EGF) to 10 and 20 ng/mL, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Embryo developmental stage was determined following HH (59). Embryos were electroporated with the indicated DNAs at 3 μg/μL with 50 ηg/mL of Fast Green as previously described (54,60). Expanded protocol is described in SI Appendix, Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation